A Role for Antimicrobial Stewardship in Clinical Sepsis Pathways: a Prospective Interventional Study. (11th July 2017) - Burston, John; Adhikari, Suman; Hayen, Andrew; Doolan, Heather; Kelly, Melissa L.; Fu, Kathy; Jensen, Tomas O.; Konecny, Pamela
Abstract : OBJECTIVE: To evaluate the impact of early infectious diseases (ID) antimicrobial stewardship (AMS) intervention on inpatient sepsis antibiotic management. DESIGN: Interventional, nonrandomized, controlled study. SETTING: Tertiary-care referral hospital, Sydney, Australia. PATIENTS: Consecutive, adult, non–intensive care unit (non-ICU) inpatients triggering an institutional clinical sepsis pathway from May to August 2015. INTERVENTION: All patients reviewed by an ID Fellow within 24 hours of sepsis pathway trigger underwent case review and clinic file documentation of recommendations. Those not reviewed by an ID Fellow were considered controls and received standard sepsis pathway care. The primary outcome was antibiotic appropriateness 48 hours after sepsis trigger. RESULTS: In total, 164 patients triggered the sepsis pathway: 6 patients were excluded (previous sepsis trigger); 158 patients were eligible; 106 had ID intervention; and 52 were control cases. Of these 158 patients, 91 (58%) had sepsis, and 15 of these 158 (9.5%) had severe sepsis. Initial antibiotic appropriateness, assessable in 152 of 158 patients, was appropriate in 80 (53%) of these 152 patients and inappropriate in 72 (47%) of these patients. In the intervention arm, 93% of ID Fellow recommendations were followed or partially followed, including 53% of cases in which antibiotics were de-escalated. ID Fellow intervention improved antibiotic appropriateness at 48 hours by 24% (adjusted risk ratio, 1.24; 95% confidence interval, 1.04–1.47; P =.035). The appropriateness agreement among 3 blinded ID staff opinions was 95%. Differences in intervention and control group mortality (13% vs 17%) and median length of stay (13 vs 17.5 days) were not statistically significant. CONCLUSION: Sepsis overdiagnosis and delayed antibiotic optimization may reduce sepsis pathway effectiveness. Early ID AMS improved antibiotic management of non-ICU inpatients with suspected sepsis, predominantly by de-escalation. Further studies are needed to evaluate clinical outcomes. Infect Control Hosp Epidemiol 2017;38:1032–1038